2021
DOI: 10.1039/d1sc04155j
|View full text |Cite
|
Sign up to set email alerts
|

Selective functionalization of the 1H-imidazo[1,2-b]pyrazole scaffold. A new potential non-classical isostere of indole and a precursor of push–pull dyes

Abstract: We report the full selective functionalization of the 1H-imidazo[1,2-b]pyrazole scaffold using a Br/Mg-exchange, as well as regioselective magnesiations and zincations with TMP-bases (TMP = 2,2,6,6-tetramethylpiperidyl), followed by trapping reactions with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the final part of this review, we describe four additional examples that are part of two rings with a fusion of type 5:5 and 5:7. Two of the works correspond to the imidazo[1,2b]pyrazole ring [75,76] and the other ones to the pyrazolo [3,4-b]azepine ring [77,78]. In these examples, the 5-or 7-membered ring is built on the respective pyrazole derivative, and, similar to the two previous examples, they are scarce fused rings to find.…”
Section: Indazoles and Other Bicyclic Pyrazole-basedmentioning
confidence: 53%
See 1 more Smart Citation
“…In the final part of this review, we describe four additional examples that are part of two rings with a fusion of type 5:5 and 5:7. Two of the works correspond to the imidazo[1,2b]pyrazole ring [75,76] and the other ones to the pyrazolo [3,4-b]azepine ring [77,78]. In these examples, the 5-or 7-membered ring is built on the respective pyrazole derivative, and, similar to the two previous examples, they are scarce fused rings to find.…”
Section: Indazoles and Other Bicyclic Pyrazole-basedmentioning
confidence: 53%
“…In these examples, the 5-or 7-membered ring is built on the respective pyrazole derivative, and, similar to the two previous examples, they are scarce fused rings to find. Regarding imidazo[1,2-b]pyrazoles, Schwärzer et al [75] reported a selective functionalization of the fused ring to obtain products 146-148 (Scheme 23a), beginning with the exchanging Br for Mg (to form 146) from the SEM-protected fused pyrazole 148 (SEM = trimethylsilylethoxymethyl), and continuing with a regioselective magnesiations (to form 147) or zinc cation (to form 148) using TMP-bases (TMP = 2,2,6,6-tetramethylpiperidyl). Precursor 144 was selectively brominated with NBS producing the 7-bromo subs tuted derivative 145, which was used as a substrate in the reaction with i-PrMgCl•LiC forming the magnesiated intermediate 145′ that then reacts with varios electrophiles (i. S-methyl sulfonothioate, tosyl cyanide, and TESCl) and by transmetallations to gi 146a-i.…”
Section: Indazoles and Other Bicyclic Pyrazole-basedmentioning
confidence: 99%